Unggul dan Bepretasi: Peningkatan Minat baca Siswa melalui Pemanfaatan Perpustakaan di MTs Salafiyah Syafi’iyah Bandung Diwek Jombang - Sunardi Sunardi; Ma`mun Abdul Latief (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2022)
The library is the most important part of an institution because the library is very far from the ancient system with now, so the use of this library is very urgent in the world of education in general and in the world of students in particular. With a library system that is used in a professional way, superior and outstanding students will be formed. This study focuses on how the model of student empowerment in reading, library management in increasing reading interest, supporting and inhibiting factors of library management in increasing students' interest in reading at MTs Salafiyah Syafi'iyah Bandung Diwek Jombang. This research is qualitative research. While the data collection techniques using observation, interviews, and documentation. The data analysis technique uses data reduction, data display, and data verification. The model of empowering students in reading at MTs Salafiyah Syafi'iyah Diwek Jombang can be simulated with several points, namely programming for reading, motivating, and coaching the reader. In the management of the library at MTs Salafiyah Syafi'iyah Diwek Jombang there are several things that are carried out as functions of management, namely planning, organizing, implementing, and supervising. The inhibiting factor for library management in increasing students' reading interest is that it can be influenced by several factors, namely management management is still not carried out optimally, collections of books or library materials have not been maximized, human resources or librarian staff, and facilities and infrastructure.